From power-blind binaries to the intersectionality of peace: connecting feminism and critical peace and conflict studies. (4th May 2019) - Kappler, Stefanie; Lemay-Hébert, Nicolas
ABSTRACT: Critical Peace and Conflict Studies scholars have increasingly sought to overcome binary approaches to engage more fully the ways in which peacebuilding missions are designed, implemented and contested. In doing so, scholars have tried to understand 'the local' and mobilised three different concepts to do so – hybridity, the everyday and narratives. However, this shift has failed to translate into fully convincing research transcending the old binaries of 'international' and 'local'. The use of the 'everyday' sees power everywhere, hybridity approaches fall into the same binary trap scholars want to avoid in the first place, and narrative approaches tend to focus on very personal stories, removing structural power from the equation. We suggest that a fruitful interaction with Feminist approaches and methodologies, and especially the scholarship on intersectionality, can help shed a new light on the power imbalances and inequalities within peacebuilding missions. We highlight the possible contribution of the concept of intersectionality to Critical Peace and Conflict Studies through an intersectionality of peace approach, which allows for a better understanding of multiple and complex identities of researchers and researchees. We illustrate this argument through a discussion of intersectional narratives centred around the space of the 'guesthouse' of South Africa.